2020
DOI: 10.22270/ujpr.v5i4.431
|View full text |Cite
|
Sign up to set email alerts
|

Vulvovaginal Candidiasis Prevalence Among Pregnant Women in Different Hospitals in Ibb, Yemen

Abstract: Background and aims: Candida species are opportunistic yeasts that affect the genital urinary tract that causes vulvovaginal candidiasis in the most females, particularly in developing countries. This work aims to find the prevalence of vulvovaginal candidiasis among pregnant women in Ibb, Yemen. Material and methods: Two hundred and eighteen samples of females attending outpatient obstetrics and gynecology clinics were chosen from several hospitals (Al-Thawra, Maternity and Childhood Center, Maternal Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…Similarly, Adjapong et al reported that 10% of C. albicans isolates from VVC patients were resistant to ITC [39]. Edrees et al showed that 29.6% of C. albicans isolates from VVC patients were resistant to ITC [40]. In addition, our findings showed that the resistance rate of C. glabrata to fluconazole was 7.7%.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, Adjapong et al reported that 10% of C. albicans isolates from VVC patients were resistant to ITC [39]. Edrees et al showed that 29.6% of C. albicans isolates from VVC patients were resistant to ITC [40]. In addition, our findings showed that the resistance rate of C. glabrata to fluconazole was 7.7%.…”
Section: Discussionsupporting
confidence: 73%
“…Edrees et al showed that 29.6% of C . albicans isolates from VVC patients were resistant to ITC [ 40 ]. In addition, our findings showed that the resistance rate of C .…”
Section: Discussionmentioning
confidence: 99%
“…According to the data in Table 1 , the highest prevalence of VVC to be noticed is 90.38% in Kenya, a study conducted by Nelson et al [ 31 ]. Also, a significant prevalence of VVC with 62.2%, 60.8% positive for candidiasis, and 61.5% positive growth in culture has been observed in Enugu State, Nigeria [ 26 ]; North-west Nigeria [ 37 ]; and Ibb, Yemen [ 28 ], respectively. On the contrary, a study performed by Masri et al [ 39 ] in Malaysia has detected the lowest positive isolates for candida, which is 17.2% during pregnancy.…”
Section: Prevalence Of Vulvovaginal Candidosis During Pregnancymentioning
confidence: 99%
“…Transmission of resistant isolates between people and/or by consumption of foods originated from animals that have received antibiotics and greater mobility of individuals worldwide has also be a factor of the expansion of antibiotic resistance. Regional differences in antibiotic resistance may be partially explained by different local antibiotic practices 50, 51 . The outcome of unnecessary and/or improper use of antibiotics on the expansion of antibiotic-resistant strains, especially of broad-spectrum agents described experimentally, has been demonstrated.…”
Section: Resultsmentioning
confidence: 99%